Heme regulates gene expression by triggering Crm1-dependent nuclear export of Bach1 - Suzuki, Hiroshi (Nature Publishing Group, 2004)
Bach1 is a transcriptional repressor of heme oxygenase-1 and β-globin genes, both of which are known to be transcriptionally induced by heme. To test the hypothesis that heme regulates the activity of Bach1, we expressed wild type and mutated versions of Bach1 together with or without its heterodimer partner MafK in human 293T and GM02063 cells and examined their subcellular localization. Inhibition of heme synthesis enhanced the nuclear accumulation of Bach1, whereas treating cells with hemin resulted in nuclear exclusion of Bach1. While the cadmium-inducible nuclear export signal (NES) of Bach1 was dispensable for the heme response, a region containing two of the heme-binding motifs was found to be critical for the heme-induced nuclear exclusion. This region functioned as a heme-regulated NES dependent on the exporter Crm1. These results extend the regulatory roles for heme in protein sorting, and suggest that Bach1 transduces metabolic activity into gene expression.